Tracing GFP-labeled WJMSCs in vivo using a chronic salpingitis model: an animal experiment - Zhe Li; Zhao Zhang; Wai-kit Ming; Xin Chen; Xiao-min Xiao (Stem Cell Research & Therapy, 2017)
Abstract Background The present study was conducted to evaluate the distribution of Wharton’s jelly-derived mesenchymal stem cells (WJMSCs) and their repairing function on the oviduct. Methods WJMSCs were transfected with the LV3-GFP-PURO lentivirus. Female New Zealand rabbits (n = 24) were divided randomly into control A and B groups and experimental C and D groups to establish inflammation models. Sterile saline solution or WJMSCs were injected into rabbits via ear veins and/or genital tract perfusion once weekly for 3 weeks. All rabbits were humanely sacrificed 1 week after the last perfusion to collect the oviduct, uterus, liver, and bladder for examination. Green fluorescent protein (GFP) and cytokeratin 7 (CK7) were imaged using a Leica Qwin Plus V3 fluorescence confocal microscope and analyzed as mean optical densities in an Image-Pro Plus analysis system. Results We found that lentivirus expressing the GFP gene produced an efficient transfection. The mean optical density values of GFP and CK7 in the oviducts were higher in the experimental D group than those in the control A and experimental C groups. No GFP fluorescence deposits occurred in the bladder of the control A group or experimental C group. Colocalization of CK7 and WJMSCs was observed in the oviducts in all groups. Conclusions WJMSCs exhibited homing characteristics and migrated to the injured oviduct to promote epithelial cell growth. Additionally, local treatment resulted in higher efficiency.